Striatal Dopamine Predicts Outcome-Specific Reversal Learning and Its Sensitivity to Dopaminergic Drug Administration - Cools, Roshan; Frank, Michael J; Gibbs, Sasha E; Miyakawa, Asako; Jagust, William; D'Esposito, Mark (The Journal of neuroscience, 2009)
Individual variability in reward-based learning has been ascribed to quantitative variation in baseline levels of striatal dopamine. However, direct evidence for this pervasive hypothesis has hitherto been unavailable. We demonstrate that individual differences in reward-based reversal learning reflect variation in baseline striatal dopamine synthesis capacity, as measured with neurochemical positron emission tomography. Subjects with high baseline dopamine synthesis in the striatum showed relatively better reversal learning from unexpected rewards than from unexpected punishments, whereas subjects with low baseline dopamine synthesis in the striatum showed the reverse pattern. In addition, baseline dopamine synthesis predicted the direction of dopaminergic drug effects. The D 2 receptor agonist bromocriptine improved reward-based relative to punishment-based reversal learning in subjects with low baseline dopamine synthesis capacity, while impairing it in subjects with high baseline dopamine synthesis capacity in the striatum. Finally, this pattern of drug effects was outcome-specific, and driven primarily by drug effects on punishment-, but not reward-based reversal learning. These data demonstrate that the effects of D 2 receptor stimulation on reversal learning in humans depend on task demands and baseline striatal dopamine synthesis capacity.